Clinical Neuropharmacology - Zeise-Ssa., M (Springer International Publishing, 2020)
The big field of clinical neuropharmacology is introduced by asking how “normal” and “disorder” are understood in the context of psychiatry followed by a very condensed classification of the most frequent mental problems. A brief introduction into pharmacodynamics and pharmacokinetics and the problems encountered in pharmacologic treatment is followed by a more detailed description of the more important groups of mental disorders, and their medical treatments including, in some cases, non-pharmacological ones. © Springer Nature Switzerland AG 2021.